Browsing recommendation based on the intertemporal choice model. - Azman, Azreen (2009)
Browsing is an important but often inefficient information seeking strategy in information retrieval (IR). In this paper, we argue that an effective recommendation model can improve the user’s browsing experience. We propose to adapt the intertemporal choice model to model the browsing behaviour of the user. The model can be used to recommend a browsing path to the users. The proposed model is based on the assumption that the browsing recommendation problem is an intertemporal choice problem. Using a simulated interactive retrieval system on several standard TREC test collections, the experimental results show that the proposed model is promising in recommending good browsing paths to the user.